Implementasi Green Accounting dalam Meningkatkan Kinerja Perusahaan - Wiwik Fitria Ningsih; Ratih Rachmawati (UNIVERSITAS INDRAPRASTA PGRI, 2017)
The purpose of this paper is to discuss how the implementation of green accounting in improving environmental performance and financial performance. Based on the discussion, it is known that the implementation of green accounting had a positive impact on environmental performance. Improved environmental performance is due to the willingness of companies to comply with government policies and regulations as well as consumer demand for a product that is environmentally friendly. In addition, the implementation of green accounting also affects the company's improved financial performance. With the increase in positive perception of society will increase the loyalty of the people against the company, which in turn was followed by an increase in the sales and profits company.Currently in Indonesia disclosure regarding environmental accounting still not specifically regulated in accounting standards, reporting environmental information in the annual reports of companies is voluntary. Therefore, in this paper, it is advisable for companies to implement green accounting. In the future, the challenge for the Indonesian Institue of Accountants to seek their statements of assets and liabilities as part of the required environment (mandatory) in the financial statements, particularly for industries that are sensitive to issues of environmental destruction.